Platelet activity with hemoglobin level in patients with hemodialysis: Prospective study. Issue 10 (March 2020) - Kim, Jae Min; Kim, Jin Sug; Kim, Hyung Oh; Lee, So Ra; Rhew, Jae Hwan; Woo, Jong Shin; Cho, Jang Hyun; Jeong, Kyung Hwan; Kim, Weon
Abstract: Background: VerifyNow (VN; Accumetrics, San Diego, CA) P2Y12 reaction unit (PRU) has an inverse relation with hemoglobin level (Hb). Chronic kidney disease (CKD) is associated with low response to clopidogrel and low Hb. Our aim is to investigate the relation between PRU and Hb, and to assess whether Hb directly affects PRU or not in patients with CKD undergoing hemodialysis (HD). Methods: We analyzed the relation between PRU and Hb in 43 HD patients and compared it with a control group of 127 patients with normal renal function. Both groups underwent percutaneous coronary intervention for stable coronary artery disease. We also compared PRU between the 2 groups considering Hb as a confounding factor. Results: In the control group, Hb and PRU showed a significant inverse correlation (correlation coefficient r = −0.340; P < .001), but not in the HD group (correlation coefficient r = −0.099; P = .53). PRU was higher in the HD group than the control group after adjusting for the influence of Hb (299.2 [95% confidence interval: 278.4–316.7] vs 248.7 [95% confidence interval: 227.7–269.0]; P < .001), even after propensity score matching (299.2 [95% confidence interval: 278.4–316.7] vs 241.7 [95% confidence interval: 221.8–262.2]; P < .001). Conclusions: PRU was higher regardless of lower Hb in CKD on HD patients than normal renal function patients. Therefore, Hb was not crucial factor to decide PRU in CKD on HD patients in this study.